Psycholinguistics: Cognitive Processes and Language Cross Interaction in Bilingualism in Educational Institutions - Sutrisno, Nina; As'ari, As'ari (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2022)
This article provides a brief review of psycholinguistic research that has been conducted to reveal the processes and representations of bilingualism that occur in a multicultural society, especially. The main conclusion from the description of the different levels of representation that has been presented both at the lexical level, semantic level, and syntactic level is that bilingual speakers always experience different languages as long as their use continues. Both bilingual speakers and speech partners benefit from the universal characteristics of the languages they master in an integrated manner. In line with this conclusion, recommendations that can be given regarding psycholinguistic research are on the study of language control and language transfer.